ENVISIONING THE FUTURE OF EDUCATION: A GLIMPSE INTO LEARNING IN 2050 AND THE ESSENTIAL CHALLENGES - Mamatursunova Marxabo; Yuldasheva Mehriyo; Egamberdiyeva Irodaxon Abdurahimovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article endeavours to explore the speculative landscape of education in the year 2050, delving into the potential impact of advanced technologies, adaptive pedagogies, and societal shifts on the learning experience. Envisioning the future of education provides a thought-provoking insight into the potential evolution of learning methodologies, the ubiquity of personalized education, and the integration of emerging technologies within the educational ecosystem.